Upaya Peningkatan Motivasi Belajar Mata Pelajaran Pendidikan Pancasila Kelas X-8 melalui Media Pembelajaran Interaktif Berbasis Canva dan Wordwall - Andriyani, Natasha Bilqies; Listyaningsih, Listyaningsih; Estuningsih, Kristiwi (CV. ULIL ALBAB CORP, 2025)
This research was conducted in classes X-8 of SMA Negeri 21 Surabaya with the aim of increasing students' learning motivation through interactive learning media based on Canva and Wordwall. Observation activities show that the method of presenting information in learning Pancasila Education is still conventional and monotonous, namely by using the lecture method. By using this method, learning is less interesting and effective in attracting students' attention while learning. As a result, students become passive listeners. Therefore, efforts are needed to create interactive learning motivation and encourage student activity during the learning process. This type of research is classroom action research with a research subject consisting of 36 students. The research data was collected using observation, interview, test, and documentation methods. After learning by applying interactive learning media based on Canva and Wordwall, students became enthusiastic about participating in Pancasila Education learning. The results of the study showed that students' motivation to learn increased. The improvement after learning using Canva and Wordwall-based learning media can be seen from the comparison of the learning motivation scores of pre-cycles, cycle I, and cycle II students. The motivation to learn in the pre-cycle was originally 42.38% with less criteria, increased to 62.41% in cycle 1 with sufficient criteria, and in cycle 2 increased to 88.44% with superior criteria. So, it can be concluded that the application of Canva-based learning media and Wordwall can increase the learning motivation of students in grades X-8 of SMA Negeri 21 Surabaya.